The Homosexual Role - McIntosh, Mary (Social Problems, 1968)
The current conceptualization of homosexuality as a condition is a false one, resulting from ethnocentric bias. Homosexuality should be seen rather as a social role. Anthropological evidence shows that the role does not exist in all societies, and where it does it is not always the same as in modern western societies. Historical evidence shows that the role did not emerge in England until towards the end of the seventeenth century. Evidence from the "Kinsey Reports" shows that, in spite of the existence of the role in our society, much homosexual behavior occurs outside the recognized role and the polarization between the heterosexual man and the homosexual man is far from complete.
Keywords: 1900-1999; 1960-1969; LGBTQIA2+; cours; discipline; homosexualité; premier cycle; périodes historiques; santé; sciences humaines; sexualité; soc2014; sociologie; thématiques

Mrs. Stevens hears the mermaids singing - Sarton, May (W. W. Norton & Company, 1965)
Le neuvième roman de May Sarton explore la lutte d'une femme pour concilier les exigences de la vie et de l'art, pour transmuer la passion et la douleur en poésie. À l'ouverture, Hilary Stevens, une poète renommée âgée de soixante-dix ans, discute avec Mar, un jeune homme intense qui l'a recherchée et dont le désespoir passionné lui rappelle elle-même lorsqu'elle était jeune. Mar a eu une histoire d'amour malheureuse avec un homme. Déconcerté à la fois par sa sexualité et par son talent d'écrivain, il jette son angoisse contre l'intelligence brusque et sympathique d'Hilary.
Keywords: 1900-1999; identités LGBTQIA2+; littérature; personnes lesbiennes; poésie; périodes historiques; roman; sexualité; thématiques